Kappa opioid receptor binding in major depression: A pilot study. Issue 9 (17th July 2018) - Miller, Jeffrey M.; Zanderigo, Francesca; Purushothaman, Priya D.; DeLorenzo, Christine; Rubin‐Falcone, Harry; Ogden, R. Todd; Keilp, John; Oquendo, Maria A.; Nabulsi, Nabeel; Huang, Yiyun H.; Parsey, Ramin V.; Carson, Richard E.; et al.
Abstract: Endogenous kappa opioids mediate pathological responses to stress in animal models. However, the relationship of the kappa opioid receptor (KOR) to life stress and to psychopathology in humans is not well described. This pilot study sought, for the first time, to quantify KOR in major depressive disorder (MDD) in vivo in humans using positron emission tomography (PET). KOR binding was quantified in vivo by PET imaging with the [ 11 C]GR103545 radiotracer in 13 healthy volunteers and 10 participants with current MDD. We examined the relationship between regional [ 11 C]GR103545 total volume of distribution (VT ) and diagnosis, childhood trauma, recent life stress, and, in a subsample, salivary cortisol levels during a modified Trier Social Stress Test (mTSST), amygdala, hippocampus, ventral striatum and raphe nuclei. Whole‐brain voxel‐wise analyses were also performed. [ 11 C]GR103545 VT did not differ significantly between MDD participants and healthy volunteers in the four a priori ROIs ( p = 0.50). [ 11 C]GR103545 VT was unrelated to reported childhood adversity ( p = 0.17) or recent life stress ( p = 0.56). A trend‐level inverse correlation was observed between [ 11 C]GR103545 VT and cortisol area‐under‐the curve with respect to ground during the mTSST ( p = 0.081). No whole‐brain voxel‐wise contrasts were significant. Regional [ 11 C]GR103545 VT, a measure of in vivo KOR binding, does not differentiate MDD from healthy volunteers in this pilot sample. Future studies may examine KOR binding in subgroups of depressed individuals at increased risk for KOR abnormalities, including co‐occurring mood and substance use disorders, as well as depression with psychotic features. Abstract : The kappa opioid system mediates dysphoric responses to stress in animals. We quantified the kappa opioid receptor (KOR) in humans with major depressive disorder using PET imaging, and observed no differences compared with healthy volunteers, shown in this graph of weighted mean binding (volume of distribution) in a priori regions.